Baṅgīẏa ranesāmse pāścātyabidyāra bhūmikā - Bandyopadhyay, Sunil, 1939- (Sārasvata Lāibrerī, 1980)
On the contribution of European scholars to and impact of western education on the reawakening of Bengal in the 19th century.